The Relationship Between Body Mass Index (BMI) and Balance in Down Syndrome Children at the X Depok Foundation - Mailani, Rena; David, Natasya Salima; Faradillah, Kiki Rezki; Ismiyasa, Suci Wahyu (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: In Indonesia, there are more than 300,000 children with Down syndrome. Down syndrome is a chromosomal abnormality that occurs while still in the womb. Children with Down syndrome have a high risk of being overweight or even obese. This increase in BMI causes various problems, one of which is the weakening of strength and loss of balance. To determine the relationship between body mass index (BMI) and balance in children with Down syndrome at Yayasan X. Methods: This study used a correlational study design with a cross-sectional approach with a sample of 89 children with Down syndrome. This research was conducted offline by using the pediatric balance scale and measuring body mass index (BMI). Results: This study used SPSS 23 and the results obtained p =0,000 on balance with the correlation coefficient between BMI of 0.559 conclusion there is a unidirectional relationship between BMI and balance. Conclusion: There is a relationship between body mass index and balance in the same direction in children with Down syndrome at Yayasan X.